Review of remediation techniques in agricultural soils contaminated by heavy metals in Latin America - Lara Ponce, Meliza Nataly (2025)
The contamination of agricultural soils by heavy metals is an environmental problem, social and economic that is currently facing Latin america, in just the past 5 years has seen a reduction in agricultural production and performance of the soil. The review article aims to analyze the techniques of bioremediation most commonly used in Latin america in agricultural soils contaminated by heavy metals, through a method of review is a systematic, selecting certain publications with a minimum of 6 years of age and performing a detailed analysis of each country. When analyzing the studies, it is evidence that the majority of Latin american countries used the technique of phytoremediation because of the advantages it offers, it's easy to obtain, the efficiency in reducing the concentration of heavy metals and low cost. Also, it is concluded that in some countries of Latin america there are no publications relating to this topic, therefore, it is assumed that it is due to the lack of motivation and implementation of scientific and technological development by universities and states of each nationality.